If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 5 = 11x + -4 Reorder the terms: 5 + 2x = 11x + -4 Reorder the terms: 5 + 2x = -4 + 11x Solving 5 + 2x = -4 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 5 + 2x + -11x = -4 + 11x + -11x Combine like terms: 2x + -11x = -9x 5 + -9x = -4 + 11x + -11x Combine like terms: 11x + -11x = 0 5 + -9x = -4 + 0 5 + -9x = -4 Add '-5' to each side of the equation. 5 + -5 + -9x = -4 + -5 Combine like terms: 5 + -5 = 0 0 + -9x = -4 + -5 -9x = -4 + -5 Combine like terms: -4 + -5 = -9 -9x = -9 Divide each side by '-9'. x = 1 Simplifying x = 1
| 3x-4-(2x+3)=0 | | 100x=0.81 | | 7500.00+155.00=92440 | | C=240+8k | | f(x)=tan^2(x)-3 | | f(x)=tan^2(x-3) | | x^3+8x^2-14x-12=0 | | 5x+10=7x-70 | | c*2+5c+4=0 | | 5y+11=28 | | 6x=178 | | e^11x+5=4 | | -15-4x=7-3 | | 18-3n=3 | | -4n+2=-2n-2 | | 8y-2=7 | | -83=2y-15y-18 | | (3x-4)(2x-9)= | | y=2(x-8)+3 | | 5u+63=8 | | 6-5(2x-3)=0 | | 8h+7=-1134 | | y=2(x-9)+3 | | 5x-20+x*-3=50 | | 2x+18=-16 | | 1=sin(2piT) | | 294-x=216 | | 10x-x^2=y | | 6x+60=50 | | 200=80-v | | -5=1-5n-n | | -7(-x+4)+10(-x)+3(-4x-2)+34= |